Integrins are Mechanosensors That Modulate Human Eosinophil Activation - Ahmadzai, Mustafa; Small, Mike; Sehmi, Roma; Gauvreau, Gail; Janssen, Luke J. (Frontiers in Immunology, 2015)
Eosinophil migration to the lung is primarily regulated by the eosinophil-selective family of eotaxin chemokines, which mobilize intracellular calcium (Ca2+) and orchestrate myriad changes in cell structure and function. Eosinophil function is also known to be flow-dependent, although the molecular cognate of this mechanical response has yet to be adequately characterized. Using confocal fluorescence microscopy, we determined the effects of fluid shear-stress on intracellular calcium concentration ([Ca2+]i) in human peripheral blood eosinophils by perfusing cells in a parallel-plate flow chamber. Our results indicate that fluid-perfusion evokes a calcium response that leads to cell flattening, increase in cell area, shape change and non-directional migration. None of these changes are seen in the absence of a flow stimulus, and all are blocked by chelation of intracellular Ca2+ using BAPTA. These changes are enhanced by stimulating the cells with eotaxin-1. The perfusion-induced calcium response (PICR) could be blocked by pre-treating cells with selective (CDP-323) and non-selective (RGD tripeptides) integrin receptor antagonists, suggesting that α4β7/α4β1 integrins mediate this response. Overall, our study provides the first pharmacological description of a molecular mechanosensor that may collaborate with the eotaxin-1 signaling program in order to control human eosinophil activation.